Parámetros físico-químicos en aguas costeras de la Isla del Coco, Costa Rica (2001-2007) - Acuña González, Jenaro (2008)
Physico-chemical parameters in coastal waters around Isla del Coco, Costa Rica (2001-2007). Four cruises to Isla del Coco (Cocos Island), Costa Rica, were carried out in order to gather oceanographic data related to surface temperature, salinity, dissolved oxygen concentration, Secchi disk depth, nutrient concentrations (nitrate, nitrite, phosphate, and silicate), chlorophyll-a, and suspended materials. Surface temperatures, salinities and dissolved oxygen concentrations were high, in the range of 26.5 to 29.7ºC, 27 to 32 psu, and 102.0 to 127.5% saturation, respectively. Phosphate was always present in the water samples, within the typical range of 0.10 to 0.53 μmol/L; the other nutrients were not detectable in some samples. Chlorophyll-a concentrations were in the range of 0.02 to 0.42 mg/m3 which revealed the influence of oceanic and coastal waters, with the higher phytoplanktonic pigment concentrations near the coast, and suspended materials from 1.08 to 17.91 mg/L. Rev. Biol. Trop. 56 (Suppl. 2): 49-56. Epub 2008 August 29.